Multiple glass pieces in paranasal sinuses - Syed Ahmed Mohiuddin; Shazia Rahiman; Shammeem Sultana (Wolters Kluwer Medknow Publications, 2011)
Here, a case has been reported of a road traffic accident with multiple glass pieces arranged in an unusual pattern in the left maxillary sinus, ethmoid sinus, nasopharynx and medial side of the orbit, as seen in the radiographs. Combined surgical approach through the existing wound and endoscopic surgery was successfully used to remove nearly all the glass pieces.